Padronização de procedimentos para a proteção da propriedade intelectual: uma contribuição a Agência de Inovação da Universidade Estadual do Oeste do Paraná - Unioeste Inova - Lazzarin, Flávia Cristina (2024)
Universities are one of the main vectors of technological innovation, producing knowledge and technology that can be converted into innovation and entrepreneurship. In this scenario, Technology Innovation Centers (NITs) play a crucial role in the protection and promotion of intellectual property (IP) rights. However, they face significant challenges, such as a reduced and unskilled staff, high employee turnover, absence of knowledge management, and difficulties in managing internal processes. The general objective of this study was to develop and propose a knowledge management mechanism at the Innovation Agency of the State University of Western Paraná, Unioeste INOVA, aiming to optimize the organization's operational processes for intellectual property protection. The approach method was qualitative-quantitative, as information was collected and processed, and the current management structure of the organization's intellectual property protection processes was analyzed. The research is classified as descriptive and explanatory regarding its objective, in order to highlight the obstacles in the procedures, their causes, and possible consequences (cause-effect). To achieve this objective, a detailed analysis of the organizational structure and the intangible assets managed by the organization was first conducted. Next, all existing IP registration and management processes were mapped and visually represented through flowcharts. Then, effective operational best practices adopted by other NITs of national public universities, references in patent application filings, with the potential to be replicated for the organization under investigation were identified. For this purpose, the benchmarking search strategy (comparative evaluation) was used. Subsequently, the operational obstacles in IP protection within the organization were diagnosed using the Ishikawa Diagram. Finally, a prognosis of IP management was conducted, presenting a set of measures for improving the processes and routines of IP registration and management for implementation in the organization, resulting in the construction of an operational manual for process improvement. The proposed measures took into account all the identified obstacles that impact the organization's operational processes of IP protection, such as organizational structure, human resources, systems, and communication, as well as the best practices identified in other national NITs. Thus, the proposed improvement actions have the potential to optimize internal processes and strengthen the organizational structure of Unioeste INOVA.